Faculty-Driven Student Engagement in Community-Engaged Projects: An Undergraduate Perspective - Sofía Espinoza Hernández; Paulina González Orozco; Nandini Yellamelli (The University of Alabama, 2023)
Increasing student involvement in community-engaged initiatives begins with cultivating an environment in which students feel safe to take intellectual risks and where their interests and assets are valued. Drawing parallels between what students are learning in the classroom and problems within real communities allows them to develop a greater sense of responsibility in addressing community needs. Furthermore, creating spaces where students can talk about what they know and what interests them offers faculty opportunities to assess what types of projects might be of interest to students. It is essential for faculty to listen to their students actively and intentionally to identify what they know, how they think, and where their interests lie when creating community-engaged projects. This article seeks to present two areas for faculty to consider when motivating students to participate in community-engaged projects and the support needed to ensure lasting community and student impact.